(untitled) (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2023)
Food and nutrition insecurity remain serious African concerns, reflecting government failure to meet global and regional human rights obligations to assure food availability, accessibility, utilisation, stability, sustainability, and agency. According to recent data, more than one-third of people facing severe food insecurity around the world live in Africa. The numbers may continue to rise in the absence of deliberate and human rightscentred solutions. The second biennial review report of the African Union on the Malabo Declaration on Accelerated Agricultural Growth and Transformation for Shared Prosperity and Improved Livelihoods conceded that the continent is not on track to meet the targets set out in the Declaration to end food insecurity and improve nutrition. This article investigates and advocates for a human rights-based approach to food andnutrition security. It highlights the critical links between the six main elements of food security, namely, availability, access, utilisation, stability, agency, and sustainability, and the normative obligations of states on the right to food and its interdependence with other fundamental human rights. It critically analyses the available legal frameworks on addressing foodinsecurity and its challenges, and proposes a human rights-based approach.